The Effect of Communication Quality, Perceived Reputation, and Relational Relationships on Loyalty through Trust as a Mediating Variable (A Study at PT Asuransi BRI Life) - Septa Vidya; Ridzki Rinanto Sigit (CV. Proaksara Global Transeduka, 2025)
The life insurance industry in Indonesia plays a strategic role in economic resilience, yet faces persistent challenges in building customer loyalty, as evidenced by high lapse rates and low persistency ratios despite strong financial performance by major players. The objective of this investigation is to assess the impact of communication quality, perceived reputation, and relational relationships on customer loyalty at PT Asuransi BRI Life, with trust acting as a mediator. A quantitative explanatory approach utilizing a survey method was adopted. Responses were gathered via Likert-scale questionnaires from 260 active customers with a minimum of one year’s tenure. Analysis via Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4.1.6 software revealed that communication quality, reputation perception, and relational relationships each exert a positive and significant influence on customer loyalty. Beyond their direct effects, communication, reputation, and customer relationships are proven to build trust. This trust is pivotal: it directly fosters loyalty and, as a mediator, channels and reinforces the influence of the other three factors. Collectively, this model explains 62.4% of the fluctuations in customer loyalty. This finding confirms that non-financial factors, especially effective communication, company reputation, and relational relationship quality, have a strategic role in building trust and increasing life insurance customer loyalty. This research provides practical implications for insurance companies in designing communication strategies and customer relationship management oriented toward strengthening long-term trust.